Effects of child care vouchers on price, quantity, and provider turnover in private care markets - Won Fy Lee; Aaron Sojourner; Elizabeth E. Davis; Jonathan Borowsky (W.E. Upjohn Institute for Employment Research, 2024)
Harnessing changes in funding for a voucher program that subsidizes consumers' use of child care services at private providers, this study quantifies effects on local markets' service capacity and prices. We also estimate how increased funding effects provider entry rate, exit rate, and highly rated provider market share. The evidence shows that an additional 100 in private voucher funding per local young child would 1) raise the number of private-provider slots by 0.026 per local young child, 2) raise average prices by 0.56 per week, mainly driven by a price increase among incumbent providers, and 3) induce new provider entry to the market by 0.4 percentage points. The estimates imply a highly elastic supply elasticity of 10.7. Thus an increase in public funding and subsequent increase in demand is expected to result in expansion of available slots accompanied by a limited increase in price.
Keywords: D24; H25; H42; J13; J22; J28; 330; child care; vouchers; prices; capacity; supply elasticity; entry rate; exit rate